Hubungan Antara Lingkar Perut dan Volume Ambing dengan Kemampuan Produksi Susu Kambing Peranakan Ettawa - Taofik, Ahmad; Depison, Depison (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The Study  was  conducted to  know  relationship  between  stomach circumference and  mammary gland  volume on milk  production  ability  of  crossing  Ettawa  goat..  The  research  used descriptif  method, the  data  were  taken  from  27  of  females  goat  at  first  lactation.  Collected  data analyzed using  simple regression  methode.   The Results  showed  that correlation  coefficient  of  stomach  circumference  and mammary  gland  Volume  had  correlation  coefisien 0,660 higher  than  correlation  coefisien  of  stomach round 0,259. So mammary gland Volume can be used as to predict milk production.